Cushing´s syndrome due to bilateral adrenal cortical disease: Bilateral macronodular adrenal cortical disease and bilateral micronodular adrenal cortical disease - Araujo-Castro, Marta; Marazuela, Mónica (Frontiers in Endocrinology, 2022)
Cushing´s syndrome (CS) secondary to bilateral adrenal cortical disease may be caused by bilateral macronodular adrenal cortical disease (BMACD) or by bilateral micronodular adrenal cortical disease (miBACD). The size of adrenal nodules is a key factor for the differentiation between these two entities (>1cm, BMACD and <1cm; miBACD). BMACD can be associated with overt CS, but more commonly it presents with autonomous cortisol secretion (ACS). Surgical treatment of BMACD presenting with CS or with ACS and associated cardiometabolic comorbidities should be the resection of the largest adrenal gland, since it leads to hypercortisolism remission in up to 95% of the cases. Medical treatment focused on the blockade of aberrant receptors may lead to hypercortisolism control, although cortisol response is frequently transient. miBACD is mainly divided in primary pigmented nodular adrenocortical disease (PPNAD) and isolated micronodular adrenocortical disease (i-MAD). miBACD can present at an early age, representing one of the main causes of CS at a young age. The high-dose dexamethasone suppression test can be useful in identifying a paradoxical increase in 24h-urinary free cortisol, that is a quite specific in PPNAD. Bilateral adrenalectomy is generally the treatment of choice in patients with overt CS in miBACD, but unilateral adrenalectomy could be considered in cases with asymmetric disease and mild hypercortisolism. This article will discuss the clinical presentation, genetic background, hormonal and imaging features and treatment of the main causes of primary bilateral adrenal hyperplasia associated with hypercortisolism.